2011
DOI: 10.1111/j.1460-9568.2010.07589.x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc enhances long-term potentiation through P2X receptor modulation in the hippocampal CA1 region

Abstract: Zn2+ is an essential ion that is stored in and co-released from glutamatergic synapses and it modulates neurotransmitter receptors involved in long-term potentiation (LTP). However, the mechanism(s) underlying Zn2+-induced modulation of LTP remain(s) unclear. As the purinergic P2X receptors are relevant targets for Zn2+ action, we have studied their role in LTP modulation by Zn2+ in the CA1 region of rat hippocampal slices. Induction of LTP in the presence of Zn2+ revealed a biphasic effect – 5–50 μm enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…Of the seven P2X subunits characterized to date (named P2 Â 1 through P2 Â 7), P2X4 receptors (P2X4Rs) are the most abundant in the central nervous system (Buell et al, 1996;Soto et al, 1996), and are expressed in neurons across multiple regions of the brain and spinal cord, as well as in microglia (Burnstock and Knight, 2004;Ulmann et al, 2008). Recent studies have pointed to the implication of P2X4 in the regulation of multiple nervous functions, including neuropathic pain (Tsuda et al, 2003;Ulmann et al, 2008), neuroendocrine functions (Zemkova et al, 2010), and hippocampal plasticity (Baxter et al, 2011;Lorca et al, 2011;Sim et al, 2006). In addition, P2X4 receptors have been recently shown to modulate the function of other major ionotropic targets, such as N-methyl-D-aspartate (NMDA) glutamate receptors (Baxter et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Of the seven P2X subunits characterized to date (named P2 Â 1 through P2 Â 7), P2X4 receptors (P2X4Rs) are the most abundant in the central nervous system (Buell et al, 1996;Soto et al, 1996), and are expressed in neurons across multiple regions of the brain and spinal cord, as well as in microglia (Burnstock and Knight, 2004;Ulmann et al, 2008). Recent studies have pointed to the implication of P2X4 in the regulation of multiple nervous functions, including neuropathic pain (Tsuda et al, 2003;Ulmann et al, 2008), neuroendocrine functions (Zemkova et al, 2010), and hippocampal plasticity (Baxter et al, 2011;Lorca et al, 2011;Sim et al, 2006). In addition, P2X4 receptors have been recently shown to modulate the function of other major ionotropic targets, such as N-methyl-D-aspartate (NMDA) glutamate receptors (Baxter et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies suggested zinc attenuated LTP in mossy fibers, 35 but another study showed LTP was enhanced by zinc in the hippocampal CA1 region. 36 Recently, Izumi et al found zinc induction of LTP at low micromolar concentrations, while attenuating it at high micromolar concentrations. Homeostasis of synaptic zinc is critical for LTP induction.…”
Section: Effects Of Nano-zno On Ltp and Depotentiationmentioning
confidence: 99%
“…This effect is mediated by a direct action via P2XRs on SBCs, which evoke membrane depolarization and calcium transients (Milenkovic et al, 2009). By increasing [Ca 2ϩ ] i , P2XRs can mediate long-term plasticity changes (long-term potentiation and long-term depression) in the CA1 pyramidal neurons of the hippocampus (Pankratov et al, 2002;Yamazaki et al, 2003;Lorca et al, 2011). Future experiments will have to clarify whether similar regulations of synaptic strength occur in developing bushy cells.…”
mentioning
confidence: 99%